Altered glucose catabolism in the presynaptic and perisynaptic compartments of SOD1G93A mouse spinal cord and motor cortex indicates that mitochondria are the site of bioenergetic imbalance in ALS. Issue 3 (22nd August 2019) - Ravera, Silvia; Torazza, Carola; Bonifacino, Tiziana; Provenzano, Francesca; Rebosio, Claudia; Milanese, Marco; Usai, Cesare; Panfoli, Isabella; Bonanno, Giambattista
Abstract: Amyotrophic lateral sclerosis is an adult‐onset neurodegenerative disease that develops because of motor neuron death. Several mechanisms occur supporting neurodegeneration, including mitochondrial dysfunction. Recently, we demonstrated that the synaptosomes from the spinal cord of SOD1 G93A mice, an in vitro model of presynapses, displayed impaired mitochondrial metabolism at early pre‐symptomatic stages of the disease, whereas perisynaptic astrocyte particles, or gliosomes, were characterized by mild energy impairment only at symptomatic stages. This work aimed to understand whether mitochondrial impairment is a consequence of upstream metabolic damage. We analyzed the critical pathways involved in glucose catabolism at presynaptic and perisynaptic compartments. Spinal cord and motor cortex synaptosomes from SOD1 G93A mice displayed high activity of hexokinase and phosphofructokinase, key glycolysis enzymes, and of citrate synthase and malate dehydrogenase, key Krebs cycle enzymes, but did not display high lactate dehydrogenase activity, the key enzyme in lactate fermentation. This enhancement was evident in the spinal cord from the early stages of the disease and in the motor cortex at only symptomatic stages. Conversely, an increase in glycolysis and lactate fermentation activity, but not Krebs cycle activity, was observed in gliosomes from the spinal cord and motor cortex of SOD1 G93A mice although only at the symptomatic stages of the disease. The cited enzymatic activities were enhanced in spinal cord and motor cortex homogenates, paralleling the time‐course of the effect observed in synaptosomes and gliosomes. The observed metabolic modifications might be considered an attempt to restore altered energetic balance and indicate that mitochondria represent the ultimate site of bioenergetic impairment. Abstract : To better characterize the energy impairment observed in synaptosomes and gliosomes purified from the spinal cord and motor cortex of SOD1 G93A and wtSOD1 mice, we evaluated the glucose catabolism upstream the mitochondrial aerobic metabolism. We observed an enhancement of glycolysis and Krebs cycle in synaptosomes, and of lactate fermentation in gliosomes from SOD1 G93A mice, suggesting that mitochondria as the site of synaptic bioenergetic impairment in ALS.